Q&A Session Following the Lecture: Marxism without Philosophy and Its Feminist Implications: The Problem of Subjectivity Centered Socialist Projects - Kolozova et al., Katerina (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Katerina Kolozova et al. Title (English): Q&A session following the lecture: Marxism without Philosophy and Its Feminist Implications: The Problem of Subjectivity Centered Socialist Projects Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 48-50 Page Count: 3 Citation (English): Katerina Kolozova et al., “Q&A session following the lecture: Marxism without Philosophy and Its Feminist Implications: The Problem of Subjectivity Centered Socialist Projects,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020): 48-50. Author Biography Katerina Kolozova, Institute of Social Sciences and Humanities - Skopje Dr. Katerina Kolozova is senior researcher and full professor at the Institute of Social Sciences and Humanities, Skopje. At the Institute, she teaches policy studies, political philosophy and gender studies. She is also a professor of philosophy of law at the doctoral school of the University American College, Skopje. At the Faculty of Media and Communication, Belgrade, she teaches contemporary political philosophy. She was a visiting scholar at the Department of Rhetoric at the University of California, Berkley in 2009, under the peer supervision of Prof. Judith Butler. She is a member of the Board of Directors of the New Centre for Research and Practice – Seattle, WA. Kolozova is the first co-director and founder of the Regional Network for Gender and Women’s Studies in Southeast Europe (2004). Her most recent monograph is Capitalism’s Holocaust of Animals: A Non-Marxist Critique of Capital, Philosophy and Patriarchy published by Bloomsbury Academic, UK in 2019, whereas Cut of the Real: Subjectivity in Poststructuralist Philosophy, published by Columbia University Press, NY in 2014, remains her most cited book.